2015
DOI: 10.1631/jzus.b1400257
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open distal pancreatectomy for benign or premalignant pancreatic neoplasms: A two-center comparative study

Abstract: (15.6% vs. 19.6%, P=0.62) was found between the groups, while the overall post-operative complication rate was lower in the LDP group (26.7% vs. 47.8%, P=0.04). Conclusions: LDP is safe and effective for benign or premalignant pancreatic neoplasms, featuring lower blood loss and substantially faster recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…The evolution of laparoscopic techniques represents one of the great leaps in the field of surgery during the past decades. It has been reported that the LDP is associated with a reduction in postoperative morbidity and shorter hospital stays in comparison with the open approach (Kooby et al, 2008;Baker et al, 2009;Briggs et al, 2009;Yan et al, 2015). In this study, patients in the LDP group experienced a similar overall morbidity as those in the ODP group.…”
Section: Discussionsupporting
confidence: 57%
“…The evolution of laparoscopic techniques represents one of the great leaps in the field of surgery during the past decades. It has been reported that the LDP is associated with a reduction in postoperative morbidity and shorter hospital stays in comparison with the open approach (Kooby et al, 2008;Baker et al, 2009;Briggs et al, 2009;Yan et al, 2015). In this study, patients in the LDP group experienced a similar overall morbidity as those in the ODP group.…”
Section: Discussionsupporting
confidence: 57%
“…EU, first reported in 1898 by Ernesto Tricomi (Howard and Hess, 2002), has been widely accepted as an alternative procedure for benign and low-grade malignant pancreatic tumors including endocrine tumors (Ramage et al, 2005;Norton, 2006;Crippa et al, 2007;Falconi et al, 2010;Hackert et al, 2011;Zhang et al, 2013), SCAs, MCNs, SPTs, branch-duct IPMNs, pseudocysts, and so forth (Talamini et al, 1998;Kiely et al, 2003;Madan et al, 2004;Papavramidis and Papavramidis, 2005;Crippa et al, 2007;Ge et al, 2010;Hackert et al, 2011;Turrini et al, 2011;Zhang et al, 2013). EU has proved to be a procedure characterized by less operation time and blood loss, faster recovery, and preserving more of the pancreas parenchyma, compared with standard procedures (Casadei et al, 2010;Falconi et al, 2010;Hackert et al, 2011;Yan et al, 2015). Yet there are some problems for the application of EUs, including PF afterwards and indications and contraindications for EUs.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective, single-center and multicenter studies have compared the outcomes between LDP and open distal pancreatectomy (ODP) [2,3,28,42,[64][65][66][67][68][69][70][71][72][73][74]. They indicated the superiority of LDP regarding blood loss, postoperative complications, such as surgical site infections, the recovery of physical function, and postoperative hospital stay.…”
Section: Laparoscopic Operationsmentioning
confidence: 99%